Waiting times in healthcare: equal treatment for equal need? - Juan David García-Corchero; Dolores Jiménez-Rubio (BMC, 2022)
Abstract Background In many universal health systems, waiting times act as a non-monetary rationing mechanism, one that should be based on clinical need rather than the ability to pay. However, there is growing evidence that among patients with similar levels of need, waiting times often differ according to socioeconomic status. The mechanisms underlying inequality in access remain unclear. Methods Using data for Spain, we study whether waiting times for primary and specialist care depend on patients' socioeconomic status (SES). Additionally, we make use of the continuous nature of our data to explore whether the SES-related differences in waiting times found for specialist consultations vary among different points of the waiting time distribution. Results Our results reveal the presence of a SES gradient in waiting times for specialist services explained on the basis of education, employment status and income. In addition, for primary care, we found evidence of a slightly more moderate SES gradient mostly based on employment status. Furthermore, although quantile regression estimates indicated the presence of a SES gradient within the distribution of waiting times for specialist visits, the SES differences attenuated in the context of longer waiting times in the public sector but did not disappear. Conclusion Our findings suggest the principle of equal treatment for equal need, assumed to be inherent to national health systems such as the Spanish system, is not applied in practice. Determining the mechanism(s) underlying this selective barrier to healthcare is of crucial importance for policymakers, especially in the current COVID-19 health and economic crises, which could exacerbate these inequalities as increasing numbers of treatments are having to be postponed.